A study of factors influencing green purchase intention among consumers in Selangor - Lai, Eva May Wah (2023)
This research aims to investigate the relationship between the factors and green purchase intention among consumers in Selangor. It is vital for firms of green products to have a greater impact to attract the consumers and understand the consumer purchase intention. I picked this topic because this research was not commonly conducted in Malaysia. The research related to the green products are still lacking in Malaysia. The researcher will explain the dependent variable which is consumer’s green purchase intention in Selangor and independent variables which are price, environmental consciousness, health concern, and product attribute are identified in the literature review by using journals, articles, and websites. The primary data was collected by questionnaires. The target population was individuals who had experience in purchasing green products and were 20 years old and above. The researcher used Software Package for Social Sciences (SPSS) version 29 to interpret reliability tests, descriptive analysis, Pearson correlation coefficient, and multiple linear regression analysis after collecting data through questionnaires. The data analysis will be performed in the form of tables. Lastly, limitations, recommendations, implications, and conclusions were included in this research.